Management of Acute Posterior Multifocal Placoid Pigment Epitheliopathy (APMPPE): Insights from Multimodal Imaging with OCTA - Mariana A. Oliveira; Jorge Simão; Amélia Martins; Cláudia Farinha (Case Reports in Ophthalmological Medicine)
A 28-year-old man presented to the emergency room with blurred vision in the right eye for two days. He reported a preceding flu-like illness one week earlier. His best-corrected visual acuity (BCVA) was 20/40 in the right eye and 20/25 in the left eye. There was no anterior chamber inflammation or vitritis in either eye. He presented multiple yellowish-white placoid lesions in the posterior pole, some involving the foveal area, bilaterally. General examination and systemic investigation were unremarkable. Multimodal evaluation with fluorescein angiography, indocyanine green angiography, and spectral domain and optical coherence tomography angiography (OCTA) were consistent with the diagnosis of acute posterior multifocal placoid pigment epitheliopathy. Due to centromacular involvement with decreased BCVA, treatment with oral methylprednisolone was started after infectious causes were ruled out. After two weeks, the patient presented functional and anatomical improvement. OCTA showed partial reperfusion of the choriocapillaris in the affected areas, in both eyes.